PERUBAHAN PERSEDIAAN HARA DAN KARBON AKIBAT KONVERSI HUTAN ALAM MENJADI LAHAN PERKEBUNAN DI SEKITAR KAWASAN TAMAN NASIONAL LORE LINDU - Muhardi Muhardi; Maman Sutisna; Muhammad Basir-cyio; Abubakar M. Lajhie (Universitas Tadulako, 2012)
Land as a limited resource has been under much pressure due to increasing population which has lead to the conversion of natural forest to satisfy their need of land. The research aim was to study changes in nutrient availability and carbon stock caused by natural forest conversion to plantation in the surrounding area of the Lore Lindu National Park. The research results showed that natural forest converted to monoculture candle nut plantation decreased soil organic matter and total carbon by up to 20% and 45%, respectively, whereas changed to cacao plantation the total carbon declined by up to 44%. Available N, P, K, Mg declined by up to 23%, 30%, 43%, and 35%, respectively, in modest agroforestry. It is recommended that either complex agroforestry or forest plantation can be developed as these types of land use lead to only slightly changes in organic matter/carbon stock and nutrient availability compared to other land use types.Key words : Agroforestry, biomass, carbon, nutrient availability.